RISK PERCEPTION & CONSUMER PURCHASE BEHAVIOUR WITH SPECIAL REFERENCE TO E-SHOPPING- AN EMPIRICAL EVIDENCE FROM INDIA (International Journal of Food and Nutritional Sciences, 2022)
Purpose: The purpose of the study is to examine the relationship between customer purchase behavior and risk perceptionTheoretical framework: Psychoanalytic Theory has been used to provide a better understanding of the impact of human perception on purchase intentionsDesign/Methodology/Approach: The primary quantitative method has been used with the help of a survey. Findings: It has been observed that India has shown a steady growth in online buying intentions Research, practical work, and social implication: E-commerce industry needs to incorporate risk management strategies to enhance perceived ease at use Originality/ Value: The value of the study is that it provides a better understanding of the customer purchase intentions